Variabilidade genética em acessos de Stylosanthes scabra Vogel e Stylosanthes viscosa (L) Sw. com base em descritores morfológicos e bromatológicos - Américo, Fabiana Karla de Araújo (2019)
The present work aimed to characterize and evaluate the genetic diversity among 81 accessions of Stylosanthes scabra Vogel. and among 90 accessions of Stylosanthes viscosa (L) Sw., stored at Embrapa Cerrados Active Forage Germplasm Bank using 24 morphological and 5 bromatological descriptors. Evaluations began 150 days after initial planting in a greenhouse. Data sets were analyzed separately for each species. Using simple averages the were made a Simpson and Shannon-Weaver Diversity Index analyzes, Multivariate Principal Component Analysis (PCA), Cluster hierarchical cluster analysis were performed using the minimum variance (Ward) and as a measure of similarity. the average Euclidean distance. Finally, an analysis of variance (ANOVA) was performed using the Tukey test (P <0.05), with repetition of the accessions within each group. The PCA of S. scabra morphological data was performed with 10 descriptors and the PCA of S. viscosa was performed with 12 morphological descriptors. In S. scabra at PCA, the first three main components accounted cumulatively for 75.78% of the total data variability and PCA of S. viscosa 76.30%. The cluster analysis separated the 81 S. scabra accessions into 3 distinct groups and the 90 S. viscosa accessions into 4 groups. For bromatological data, of PCA of S. scabra in the first three main components accounted cumulatively for 86.75% of the total data variability and in S. viscosa PCA 81.02%. The dendrogram separated into 4 distinct groups the 81 accessions of S. scabra and in 4 groups the 90 accessions of S. viscosa. It was possible to confirm the existence of genetic variability among the accessions analyzed. All descriptors used in PCA are suggested here as a starting point for characterizing the variability of the species analyzed. Some accessions evaluated in this work have important characteristics regarding their use in the breeding and selection process of new cultivars.